Новые данные о суслике малом (Citellus pygmaeus Pall.) Северного Кавказа - Иванов, И.В.; Темботов, А.К. (Вестник зоологии, 1973)
A new settlement of Citellus pygmaeus P a l l., found on Jinalskian ridge, in the Podkumok and Malka interfluve (to the South-East of Kislovodsk), is of the plain origin. The animals inhabit the upper band of the above-mentioned ridge within the limits from 1000 to 1400 m above the sea level. Many peculiarities of C. pygmaeus P all. life and some morphophysiological indices testify to the young age and plain origin of this Jinalskian population. An analysis of morphophysiological indices in different populations of C. pygmaeus P a 1 1. from the Northern Caucasus carried out in 1970 confirms once more the opinion of some authors on the presence in the animals of two levels of adaptation to the high-mountain conditions as well as the opinion of the article's authors on the possibility of settling the high-mountains of the Central Caucasus with the plain species under modern lands¬cape conditions.